DEVELOPMENT OF COMMUNICATION STRATEGY FOR ENHANCING PUBLIC AWARENESS OF TUBERCULOSIS - Wihastuti, Titin Andri; Utami, Yulian Wiji (Caring: Jurnal Pengabdian Masyarakat, 2024)
Tuberculosis (TB) remains a significant global health issue, particularly in Indonesia, where lack of awareness and knowledge about TB hinders efforts to control its spread. In the Manggarai region, Nusa Tenggara Timur, the geographical diversity and limited infrastructure further complicate health education efforts. This community service activity aimed to increase awareness, knowledge, and understanding of TB among the Manggarai community through effective communication strategies. Method: The initiative involved a collaboration between the Faculty of Health Sciences Universitas Brawijaya (FIKES UB) and the Manggarai Health Office. The methods included conducting a Forum Group Discussion (FGD) to analyze the situation, followed by four hybrid sessions of communication training, distribution of TB-themed merchandise, and ongoing monitoring and evaluation. Result: The activities led to a noticeable improvement in community awareness, knowledge, and understanding of TB. Additionally, several key barriers to TB control in the region were identified and addressed through this initiative. Conclusion: The program successfully enhanced TB awareness,  knowledge, and understanding in Manggarai, highlighting the importance of targeted communication strategies in overcoming health education challenges in regions with limited infrastructure.